Modelagem computacional de um equivalente dinâmico para o sistema elétrico New England - Camarotto, Antônio Carlos Pereira (Universidade Federal do Tocantins, 2017)
This work was based on the methodology developed for computer modeling of dynamic of electric power systems equivalents presented in BRITO, 2009 [5]. And in this work we developed a method of modeling of dynamic equivalents of electric power systems with generators, machines and their controllers. The dynamic equivalent consists of a substitution of a portion of an Electric Power System, consisting of transmission lines, the load buses and generating bars, so that these will be synthesized and minimized so that the number of elements is decreased, but retain the electric dynamic behavior of the original area, with the closest to the found in the electrical system of original power. Theoretical calculations for obtaining the static and dynamic equivalents of said power system were performed. For that use the ANAREDE program to obtain the results of the full system load flows and reduced system. These results were used in a parsing program small disturbances, called PACDYN, which checks the dynamic behavior of the system. To enable this analysis has included a small voltage perturbation in the system, next to its angular reference bar. The results found by PACDYN program were exported to a mathematical analysis and simulation program called MATLAB, which graphs the results obtained and applied the technique of least squares were generated to adjust the results. By comparing the equivalent of complete systems and power flows obtained if the validation work, by using the New England system as test system. In this paper we apply the methodology developed in BRITO, (2009) [5] in the New England power test system, complementing the original work, in which the inside and outside of the system, chosen to build the dynamic equivalent were joined by a single border bar. In our work we use an area which required us to use four border bars, four transmission lines and a dummy coupling bar, which was connected to the equivalent generator and equivalent charges. Comparing the results of the full and reduced system obtained values close enough to demonstrate the robustness of the dummy system and to validate again the methodology.